2014
DOI: 10.1007/s13277-014-2891-z
|View full text |Cite
|
Sign up to set email alerts
|

SMYD3 overexpression was a risk factor in the biological behavior and prognosis of gastric carcinoma

Abstract: SET and MYND domain-containing protein 3 (SMYD3), a histone methyltransferase, plays a key function in the progression of human cancer. However, the role of SMYD3 in gastric carcinoma carcinogenesis has yet to be elucidated. This study aimed to determine the relationships of SMYD3 expression with clinicopathological characteristics and prognosis in gastric carcinoma. The expression of SMYD3 was detected by real-time quantitative reverse transcription PCR and Western blot in gastric carcinoma (GC) cell lines, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 25 publications
1
18
1
Order By: Relevance
“…We also demonstrated that SMYD3 overexpression increased glioma cell proliferation and promoted tumorigenesis in vitro, whereas SMYD3 knockdown by shRNA inhibited tumorigenesis. These data are consistent with a recent study that investigated the function of SMYD3 in gastric and breast cancers (26,27). All of these findings are supported by a recent study, which reported that the overexpression of SMYD3 protein in breast cancer alters tumor cell fate and promotes tumor progression (27).…”
Section: Discussionsupporting
confidence: 92%
“…We also demonstrated that SMYD3 overexpression increased glioma cell proliferation and promoted tumorigenesis in vitro, whereas SMYD3 knockdown by shRNA inhibited tumorigenesis. These data are consistent with a recent study that investigated the function of SMYD3 in gastric and breast cancers (26,27). All of these findings are supported by a recent study, which reported that the overexpression of SMYD3 protein in breast cancer alters tumor cell fate and promotes tumor progression (27).…”
Section: Discussionsupporting
confidence: 92%
“…SET and MYND domain‐containing protein 3 (SMYD3) is a protein lysine methyltransferase, and is overexpressed in a wide range of cancers, including breast, colorectal, hepatocellular, lung, and pancreatic carcinomas . Several lines of evidence have indicated that SMYD3 plays a pivotal role in human tumorigenesis through methylation of histone and nonhistone protein substrates . In this study, we demonstrated trimethylation of a lysine 175 residue of HER2 by SMYD3, which may affect the HER2 homodimerization and the activation of its downstream pathways.…”
Section: Introductionmentioning
confidence: 72%
“…As mentioned above, we and other groups reported that SMYD3 was highly expressed in various types of human cancer , and is implicated to have an oncogenic function . However, the biological significance of nonhistone protein methylation by SMYD3 has not been well characterized.…”
Section: Discussionmentioning
confidence: 93%
“…SMYD3 is located on human chromosome 1 and encodes two protein isoforms that are composed of 428 and 369 amino acids. Previous studies have demonstrated that SMYD3 is frequently overexpressed in numerous types of cancer cells, including hepatic, colon, gastric and cervical carcinoma, and breast cancer (2)(3)(4), whilst the expression levels were lower in the corresponding normal tissue. A number of previous studies have demonstrated that SMYD3 has vital roles in the process of tumor development via its functions as a histone methylation enzyme and a transcription factor (5,6).…”
Section: Introductionmentioning
confidence: 97%